2007
DOI: 10.1128/jcm.02016-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dried Blood Spots for Human Immunodeficiency Virus Type 1 Drug Resistance Testing

Abstract: Dried blood spots (DBS) are simpler to prepare, store, and transport than plasma or serum and may represent a good alternative for drug resistance genotyping, particularly in resource-limited settings. However, the utility of DBS for drug resistance testing is unknown. We investigated the efficiency of amplification of large human immunodeficiency virus type 1 (HIV-1) pol fragments (1,023 bp) from DBS stored at different temperatures, the type of amplified product(s) (RNA and/or DNA), and the similarity betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
116
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 24 publications
11
116
0
Order By: Relevance
“…Few studies examined the possibilities of performing drug resistance testing on dried blood, plasma, or serum on filter paper (24,33,43). Because of the ease to collect, store, and transport DBS, use of DBS is the ideal method for blood sampling in resource-poor rural settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies examined the possibilities of performing drug resistance testing on dried blood, plasma, or serum on filter paper (24,33,43). Because of the ease to collect, store, and transport DBS, use of DBS is the ideal method for blood sampling in resource-poor rural settings.…”
Section: Discussionmentioning
confidence: 99%
“…Results of published reports in this regard are very inconsistent (6,10,14,21,24,34). The present study aims to investigate both the possibility of DNA sequencing from whole blood cells or from DBS and the usefulness of DNA sequencing for determination of drug resistance in patients from a resource-poor setting with a high level of HIV-1 subtype diversity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that high-quality sequencing data could be obtained from DBS stored at −20˚C for 5 to 6 years but not from DBS stored at room temperature (53). There was also good agreement of sequencing data obtained from stored DBS compared to the stored plasma samples (54). The size of the amplicon also influences the quality of sequencing; only 58% of DBS stored at 4˚C for one year could be amplified using the ViroSeq test, which generates an 1800-base-pair amplicon, compared to a 95% success rate using a laboratorydeveloped assay that amplifies a 1000-base-pair fragment (55).…”
mentioning
confidence: 79%
“…The size of the amplicon also influences the quality of sequencing; only 58% of DBS stored at 4˚C for one year could be amplified using the ViroSeq test, which generates an 1800-base-pair amplicon, compared to a 95% success rate using a laboratorydeveloped assay that amplifies a 1000-base-pair fragment (55). DBS may be a good alternative for resistance testing, although proviral DNA can contribute significantly to the viral sequences (54), and storage conditions are critical (56).…”
mentioning
confidence: 99%